(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article investigates the role of the gender equality concept within the framework of social institutions’ activities in the context of socio-political and economic development. The study provides a scientific substantiation of the roles played by the family, education, and mass media in the process of individual socialization, the social constructive nature of gender roles, and the necessity of institutional transformations.